Antimicrobial Resistance and Genetic Relatedness of Escherichia coli Isolated from Fecal Poultry and Bovine Housed in Tunisian Farms - Hajer Kilani; Mohamed Salah Abbassi; Sana Lengliz; Rim Dhifalli; Bouraoui Jihene; Riadh Mansouri; Noureddine Ben Chehida; Ilhem Boutiba-Benboubaker (Research Perspective on Biological Science Vol. 4, 2025)
This study aimed to investigate the presence of integrons in commensal E. coli isolates from animal origins (poultry and bovine) housed in farms located in four different governorates of Tunisia (Sousse, Tunis, Bizerte and Gbeli), with a focus on antimicrobial resistance of the isolates and phylogroups as well as genetic characterization of genes encoding sulphonamides, tetracycline resistance (owing to their high rates of resistance in our collection and their excessive use in veterinary medicine in Tunisia). Mobile genetic elements such as plasmids, transposons, and integrons are able to disseminate genes encoding antibiotic resistance by horizontal transfer, and play an important role in the evolution and dissemination of multidrug resistance in Gram-negative bacteria. Little detailed documentation has been researched on the excessive use of antimicrobials such as tetracycline and sulfonamides in veterinary medicine in Tunisia, and more studies are needed. A total of 58 commensal Escherichia coli isolates recovered from faecal samples of healthy poultry (n=31) and bovine (n=27) recovered from farms in Tunisia were examined for 20 antimicrobials as well as researched the presence of integron, variable regions (VRs), phylogroups, tetracycline (tetA, tetB, et tetC) and sulfonamides (sul1, sul2, and sul3) resistance genes. The most frequent resistance in poultry origin was to tetracycline (94.3%), sulfonamide (70.69%), nalidixic acid (61.29), trimethoprim-sulfamethoxazole and streptomycin with 64.51%, to amoxicillin and ticarcilline with 58%. Whereas, for the bovine isolates, it noted high resistance to streptomycin (55.5%) and moderate resistance to tetracycline (37%) and amoxicillin (18.5%). Class 1 integrons were detected in 20, 6 isolates for poultry and bovine, respectively, as well as class 2 integrons were found in 2 and 1 isolates, respectively. Class 1 integrons were significantly associated with poultry origin (p=0.001). For poultry, sul1, sul2, and sul3 genes were detected in 14 (46.2%), 7 (23.8%), and 4 (8.9%) resistant isolates, respectively. Whereas, for bovine, 5 isolates were resistant to sulfonamide and sul1 and sul2 genes were detected in 4 and 1 isolates, with an absence of sul3 genes. and tetracycline genes tetA, tetB genes were observed in 27 (84.37%) and 8 (25%) resistant isolates, respectively, while TetC was not detected amongst our isolates. Seven arrangement gene cassettes were detected; dfrA1-satA1-aadA1 in one identical DNA fragment with approximate size of 2000 bp, and six arrangements of resistance gene cassettes of class 1 integron were detected; dfrA1+aadA1 (5isolates); for dfrA17+aadA1, dfrA12+ orfF+aadA2 each one two 2isolates; one isolate for aadA1 and dfrA5, respectively. In poultry, 16 isolates were found to belong to phylogroup A (subgroupA1: 12, subgroupA0: 4); 9 to B1, 1 to B2 and 5 to phylogroup D. However, in bovine 9 isolates have the phylogroups A1, 7 isolates B1, 4 isolates B2, and 3 isolates found to phylogroup D. Our results showed that the prevalence of resistance in E. coli isolates from poultry was much higher than that observed in bovin. This is worrisome for global human health, especially with the increasing consumption of poultry meat in Tunisia and in another part of the world owing to its relatively lower cost compared to red meat.